THE WAYS OF INCREASE OF THE MODEM ARC STEEL-MAKING FURNACES CAPACITY - V. A. Matochkin; V. Ju Gunenkov; D. N. Andrianov; A. I. Rozhkov (Литьë и металлургия, 2005)
The main ways of intensification of melting processes in the modern high-capacity electric arc furnaces of alternating current are examined, their advantages in the field of application are shown.